Release of xenon-137 and iodine-137 from UO/sub 2/ pellet by pulse neutron irradiation at NSRR - "Ishiwatari, N"; "Nagai, H [Japan Atomic Energy Research Inst., Tokai, Ibaraki. Tokai Research Establishment]" (1981)
A radiochemical procedure was established to estimate the amount of volatile fission products nuclides released from UO/sub 2/ pellet by the pulse neutron irradiation at the NSRR. The /sup 137/Cs amounts in the fuel rods after irradiation at the NSRR were measured to clarify release behavior of fission products (/sup 137/Xe and /sup 137/I) from oxide fuel under the reactivity initiated accident condition. The amounts of /sup 137/Xe and /sup 137/I released from the UO/sub 2/ pellet were estimated from the measurement of /sup 137/Cs. All UO/sub 2/ pellets before irradiation at the NSRR were fresh. The nuclides of /sup 137/Xe and /sup 137/I generated in UO/sub 2/ pellet of fuel rod by irradiation at the NSRR were released from the pellet in relation with the vaporization phenomenon after melting of UO/sub 2/ pellet. At the deposition energy higher than 340--350cal/g UO/sub 2/, about 60% of /sup 137/Xe and /sup 137/I were released from the pellet of fuel rod, at maximum. At the deposition energy lower than 340 --350cal/g UO/sub 2/, /sup 137/Xe and /sup 137/I in the UO/sub 2/ pellet of fuel rod were scarcely released out.
Keywords: "22 GENERAL STUDIES OF NUCLEAR REACTORS"; "CESIUM 137"; "FISSION YIELD"; "FUEL PELLETS"; "FISSION PRODUCT RELEASE"; "IODINE 137"; "URANIUM DIOXIDE"; "EXPERIMENTAL DATA"; "FISSION PRODUCTS"; "IRRADIATION"; "LEAKS"; "NSRR REACTOR"; "PULSED NEUTRON TECHNIQUES"; "XENON 137"; "ACTINIDE COMPOUNDS"; "ALKALI METAL ISOTOPES"; "BETA DECAY RADIOISOTOPES"; "BETA-MINUS DECAY RADIOISOTOPES"; "CESIUM ISOTOPES"; "CHALCOGENIDES"; "DATA"; "ENRICHED URANIUM REACTORS"; "EVEN-ODD NUCLEI"; "HOMOGENEOUS REACTORS"; "HYDRIDE MODERATED REACTORS"; "INFORMATION"; "INTERMEDIATE MASS NUCLEI"; "IODINE ISOTOPES"; "ISOTOPES"; "MATERIALS"; "MINUTES LIVING RADIOISOTOPES"; "MIXED SPECTRUM REACTORS"; "NUCLEAR REACTION YIELD"; "NUCLEI"; "NUMERICAL DATA"; "ODD-EVEN NUCLEI"; "OXIDES"; "OXYGEN COMPOUNDS"; "PELLETS"; "PULSED REACTORS"; "RADIOACTIVE MATERIALS"; "RADIOISOTOPES"; "REACTORS"; "RESEARCH AND TEST REACTORS"; "RESEARCH REACTORS"; "SECONDS LIVING RADIOISOTOPES"; "SOLID HOMOGENEOUS REACTORS"; "URANIUM COMPOUNDS"; "URANIUM OXIDES"; "WATER COOLED REACTORS"; "WATER MODERATED REACTORS"; "XENON ISOTOPES"; "YEARS LIVING RADIOISOTOPES"; "YIELDS"; "220300* - Nuclear Reactor Technology- Fuel Elements"